The effectiveness of health care provider physical activity recommendations in cancer survivors: a systematic review and meta-analysis protocol - Brunet, Jennifer; Wurz, Amanda; O’Rielly, Connor; Howell, Doris; Bélanger, Mathieu; Sussman, Jonathan (Université d'Ottawa | University of Ottawa, 2017)
Abstract Background Cancer survivors face a range of negative physical and psychological effects that can be mitigated by participating in physical activity. Despite this, most do not meet recommended levels. Health care providers may be in a unique position to promote participation in physical activity among cancer survivors. The aim of this systematic review and meta-analysis is to synthesize the findings from randomized controlled trials and controlled clinical trials investigating the effectiveness of health care provider-administered physical activity recommendations on participation in physical activity among cancer survivors. Methods/design Ten electronic databases (CINAHL, CENTRAL, Education Source, EMBASE, LILACS, MEDLINE, OTSeeker, PEDro, PsycINFO, SPORTDiscus) will be searched to identify relevant studies. The electronic searches will be supplemented by scanning the reference lists of relevant articles retrieved during these searches to ensure all potentially relevant studies are identified. Two reviewers will independently screen all titles and abstracts resulting from the searches to identify potentially eligible studies. They will then screen the full-text articles passing the first screen to identify studies for inclusion using predetermined inclusion/exclusion criteria, extract data from studies meeting all criteria, and assess the risk of bias of these studies. Results will be summarized narratively and statistically. Discussion By summarizing the best available evidence for the effectiveness of health care provider physical activity recommendations for increasing participation in physical activity among cancer survivors, the results of this systematic review and meta-analysis will help determine if making physical activity recommendations effectively changes cancer survivors behaviour. It will also help to identify knowledge gaps and highlight areas in need of additional research.